Crop yield and quality of brewer’s barley depending on the (Hordeum vulgare L. sensu lato) way of gathering - Г. П. Жемела; Ю. М. Барат (Plant Varieties Studying and Protection)
Influence of harvesting ways of spring brewer’s barley on grain crop capacity and quality has been examined. It has been established that in order to get good quality grain and timely harvesting all yield along with direct combine operator usage, application of separate way during grain humidity is acceptable.